2019
DOI: 10.1002/tal.1632
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on seismic performance of T‐shaped partly precast reinforced concrete shear wall with grouting sleeves

Abstract: Summary Prefabricated structure has prominent advantages such as easy control of construction quality, saving fabricating time and natural resources, and reducing environmental pollution and construction noise. The mostly used structural system in high‐rise buildings is reinforced concrete shear wall structure, which has high load capacity and lateral stiffness. Focusing on the connection of reinforcements, three T‐shaped partly prefabricated reinforced concrete shear walls and one cast‐in situ specimen in sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…e connections of the precast concrete shear wall components were crucial to the mechanical performance of the structure [5], and the vertical connection affects the integrity and energy dissipation of the buildings. Previous studies and analyses have shown that the precast concrete shear walls have the dominant bearing capacity and energy dissipation [6,7]. According to the criterion of the American, European, Chinese, and Japanese standards, the performance of some precast concrete shear walls can reach the level of cast-in-situ shear walls [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…e connections of the precast concrete shear wall components were crucial to the mechanical performance of the structure [5], and the vertical connection affects the integrity and energy dissipation of the buildings. Previous studies and analyses have shown that the precast concrete shear walls have the dominant bearing capacity and energy dissipation [6,7]. According to the criterion of the American, European, Chinese, and Japanese standards, the performance of some precast concrete shear walls can reach the level of cast-in-situ shear walls [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The PC model attained a good integrity and complied with the requirements of the current seismic design code. Lu et al 11,12 and Li et al 13,14 studied the seismic performance of precast concrete shear walls with different joints and shapes. Results show that the presented PC shear walls have good integrity and reliable seismic performance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, different types of shear walls have been studied, including linear type, I-shaped, L-typed, and T-shaped. Several studies focused on the influence on the seismic behavior of these shear walls exerted by the following factors: the length of the splicing zone, the length of the ribs, the material of the splicing zone, and the form of the splicing zone(Sun et al [11], Song et al [12], LU et al [13], JGJ101-96 [14], Smith et al [15], Pekau et al [16], Soudki et al [17], LI et al [18], Soudki et al [19]). Nevertheless, there are few studies on the prefabricated frame-shear structure.…”
Section: Introductionmentioning
confidence: 99%